MARKETING INNOVATION IN THE DIGITAL ERA: INCREASING CAPITAL AT STIKOM CKI THROUGH TECHNOLOGY AND SOCIAL MEDIA - Muhammad Farrel Ardan; Harimukti Wandebori (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Purpose - Marketing innovation in the digital era is increasingly decisive for the institutional capital of small private higher education institutions (HEIs) in developing economies. This study examines how STIKOM CKI, a small private ICT institution in East Jakarta, Indonesia, can leverage digital marketing to reverse declining enrollment and strengthen institutional capital. Design/methodology/approach - The study adopts a qualitative single-case design that triangulates semi-structured interviews with institutional management and current students, document analysis of internal records, and netnographic observation of the institution's official digital channels. Evidence was analysed thematically and mapped onto established strategic frameworks (RBV, VRIO, Value Chain, PESTEL, Porter's Five Forces, and SWOT/TOWS). Findings - Institutional data confirm a structural enrollment decline of 39% between 2020/2021 and 2024/2025, driven primarily by low brand awareness and under-utilised digital tools rather than by academic quality. The study develops a Digital Marketing Higher Education Strategic Framework resting on five pillars: SDGs-MSME differentiation, a prioritised multi-channel presence (TikTok, Instagram, YouTube, LinkedIn, Google Search, WhatsApp Business), community-based marketing, micro-credential innovation, and data-driven improvement. A phased twelve-month implementation plan with measurable KPIs is proposed at an estimated annual investment of Rp 120,000,000-Rp 170,000,000. Originality/value - The study contributes to the limited literature on digital marketing for small private HEIs in developing economies, demonstrating how SDGs-MSME alignment can function as a rare and inimitable competitive differentiator rather than a peripheral commitment.